1988
DOI: 10.1111/j.1751-0813.1988.tb14457.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of media used for the primary isolation of Mycobacteriurm bovis by veterinary and medical diagnostic laboratories

Abstract: Veterinary and medical laboratories engaged in the cultural diagnosis of bovine or human tuberculosis were requested to supply samples of the media that they routinely use for the primary isolation of M. bovis. Fourteen laboratories supplied 7 basic media types; these were Lowenstein-Jensen, Stonebrink's, modified Middlebrook 7H11 agar, tuberculosis bovine blood agar, egg yolk agar, Gerloff's egg and Herrold's egg yolk. Two strains of M. bovis were used to test the media, strain AN5, a glycerol-tolerant labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
2
11
0
5
Order By: Relevance
“…The number of isolates and colonies were higher on B83, ST and LJp, confirming findings of previous studies (CORNER ;NICOLACOPOULOS, 1988;COUSINS et al, 1989). According to our data, seven M. bovis isolates grew only on ST, five only on LJp and four only on B83.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The number of isolates and colonies were higher on B83, ST and LJp, confirming findings of previous studies (CORNER ;NICOLACOPOULOS, 1988;COUSINS et al, 1989). According to our data, seven M. bovis isolates grew only on ST, five only on LJp and four only on B83.…”
Section: Discussionsupporting
confidence: 81%
“…B83 and ST exhibited similar results in terms of faster detection, which supports Corner's (1994) data from studies using 491 samples, though other investigations showed lower time to first appearance of colonies on 7H11 (COUSINS et al, 1989;CORNER et al, 2012) and Middlebrook 7H11 medium with addition of antibiotics (GALLAGHER;HORWILL, 1977;CORNER;NICOLACOPOULOS, 1988).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The prevalence of FGTB in infertility clinics has been reported to range from 1 to 19% (2,11,13). In addition to M. tuberculosis infection, M. bovis infection has been reported to occur in FGTB (4, 7).The failure to isolate M. bovis in the present study may be due to use of inappropriate media (5,6). Nonspecific clinical presentation, inefficacy of laboratory diagnostic tests, and inaccessibility of reproductive clinics have resulted in underreporting of FGTB.…”
mentioning
confidence: 37%